Analisis Pencemar PM10 pada Udara Ambien Akibat Aktivitas Kendaraan Bermotor: Studi Kasus: Jalan Poros Puuruy-Morosi, Desa Puuruy, Kecamatan Morosi, Kabupaten Konawe - Nurhalifa, Nanda; Ilham, Ilham; Sumarlin, Sumarlin (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
Indoor and outdoor air pollution (indoor and outdoor pollution), Dust is often used as an indicator of environmental pollution indicating the level of danger to the environment, Particulate Matter PM10 is one of the air pollutants classified as primary pollutant, Pollutants Released Directly into Air from Pollution Sources Such as motor vehicle activity. PM10 particulate matter levels were measured using an Air Quality Monitor. This study shows the concentration of PM10 on Jalan Poros Puuruy Morosi in the morning reached 51.63 g/Nm3, 39.91 g/Nm3, and was still in safe levels for humans. However, in the afternoon the concentration of PM10 particulate matter increased and reached 97.83 μg/Nm3 exceeding the quality standard of 75 μg/Nm3.